2023
DOI: 10.3390/w15010191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Influence of Catchment Parameters on the Required Size of a Stormwater Infiltration Facility

Abstract: One sustainable method of stormwater management is surface infiltration with retention. Proper design of stormwater infiltration facilities ensures a reduction in flood risk within urban catchments. However, this is not possible without considering the key design parameters of such facilities. The aim of this paper is to determine the influence of the parameters characterizing the catchment area on the size of the stormwater infiltration facilities. The research used SWMM 5.1 and Statistica software. It was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 67 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…This study was conducted according to the procedure shown in Figure 1. As in the previous stage of the analysis [35], the required area of the stormwater infiltration facility was determined using SWMM 5.1 software (EPA SWMM, Cincinnati, Ohio, USA). The development of the research plan was made possible by using Statistica software (TIBCO Statistica, Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted according to the procedure shown in Figure 1. As in the previous stage of the analysis [35], the required area of the stormwater infiltration facility was determined using SWMM 5.1 software (EPA SWMM, Cincinnati, Ohio, USA). The development of the research plan was made possible by using Statistica software (TIBCO Statistica, Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies by the authors [35] showed that the total catchment area (A c ), the type of soil within it, and the percent of impervious area (C) are of key importance in the design process of stormwater infiltration facilities. On the other hand, the importance of the other parameters considered in the analysis, such as the depth of depression storage (h d ), length of the system (L d ), average slope of the catchment surface (i s ), catchment load (L c ), average slope of the conduits' bottom (i c ), catchment roughness coefficient (n c ), or number of subcatchments (n s ), is significantly lower.…”
Section: Research Planmentioning
confidence: 99%
See 1 more Smart Citation
“…The filtration layer prevents substrate particles from entering the drainage layer. The bottom of the filter-insert is also lined with a filter layer (15), in the form of a non-woven fabric, whose task is to prevent the drainage layer particles from penetrating through the flow holes.…”
Section: Characteristics Of a New Bioretention Drainage Channel Solutionmentioning
confidence: 99%
“…LID refers to techniques and principles that aim to reduce stormwater runoff into sewers, recharge groundwater, increase infiltration, and protect rivers and watercourses. Achieving these goals enables the use of solutions such as retention reservoirs [12,13], infiltration facilities and devices [14,15], and rainwater-harvesting systems [16,17].…”
Section: Introductionmentioning
confidence: 99%